Aprender a empreender: a pedagogia empreendedora do SEBRAE - Pinheiro, Dalessandro de Oliveira (2010)
This study is the object of study the course "Learning to undertake," SEBRAE, one of the tools for the dissemination of ideas of entrepreneurship in Brazil. In the 1990s, with the effects of neoliberalism on the world of work, especially the high unemployment rates, capital printed on the working class successive blows to the rights and conditions of production of material life. On the one hand the demand for a "new worker", polyvalent, making use not only of their physical and technical, but all their attributes and abilities as a human being, his "skills". On the other, the exacerbation of the farm to meet the demands of global competition for markets. Then, based on the discourse of employability and entrepreneurship, SEBRAE is now used as a tool to strengthen political and ideological direction of the capital. Its course "Learning to undertake 'return to the working class in perspective, a reality of structural unemployment, offer workers the opportunity to" be master of himself. " The proposed objectives in the development of the research are: 1) examine the issue conceptual and material conditions that made possible the development of entrepreneurial ideas in the country, 2) analyze the relationship between the institution SEBRAE its course "Learning to Engage," and other vectors in an attempt to contribute to the spread of the entrepreneurial culture in Brazil, 3) analyze the characteristics of the Entrepreneurial Education SEBRAE in spreading the motto "Be your Boss!", 4) analyze how the speech goes against the entrepreneurial skills of speech and employability. The research was developed through analysis of the teaching material of the course "Learning to undertake," especially the video lessons and Participant's Manual, taken as primary sources. As for secondary sources, we use literature related to entrepreneurship, particularly those of a liberal and, in counterpoint, readings that are inconsistent with the historical materialistic perspective and addressing the critical issue. The first chapter presents considerations on the national scene in 1990 and the conditions that allowed the diffusion of entrepreneurial ideas in the country, in the second chapter, this was SEBRAE and of course "Learning to undertake" as well as other vectors, such as capital instruments geared to entrepreneurship, in the third chapter, the primary sources are explored, highlighting the main categories and entrepreneurial characteristics highlighted by the course "Learning to undertake" the fourth chapter discusses the feasibility of the proposed "Learning to Undertake "as an alternative to generate employment and income and the weakening of the notion of qualification ahead of strengthening the ideals of entrepreneurship. Thus, we find some gaps in entrepreneurial discourse to characterize it as restricted to the human, and as of extreme insecurity for workers.